Social Criticism in the Text Scripture of Dharmasonya - Aryanto, Aris; Sudardi, Bani; Purwasito, Andrik; Wakit, Abdullah (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
This study took a closer look at the socio-condition of the Javanese people in Surakarta at the time Dharmasonya (Ds) text was produced through a perspective of critical-sociological studies. The present Ds text was read through seeing the historical life of the Islamic religion. The main objective of this study was to probe socio-cultural life of the society in the age the Ds text was produced. The data source used was the translation of Ds text by Suratmin which was issued by the Ministry of Education and Culture. To obtain the objectives, study on the Ds text was compared with other similar ancient texts of the same themes produced in the same time; these texts were Serat Wedhatama by KGPAA Mangkunegara IV (1853-1881) and Serat Tjemporet by R.Ng. Ranggwarsita. The data was analyzed through perspectives of Hermeneutic and Semiotics methods. The result shows that in Ds text, social criticism was an attempt to resist against the dynamic circumstances faced by the society at the time wherein the social status and nobility became people’s life concern. Such circumstance has apparently been used at least by a stream of Islamic group to write religious text in literary form, since religious doctrine was considered as one of the powerful weapons to control the society. Thus, most people would forcefully obey and submit to the teachings of Islam based on the Sharia law.